A Qualitative Exploration of Counselor Educators' Collaborative Authorship Perceptions and Practices. Issue 2 (11th October 2020) - Swank, Jacqueline M.; Houseknecht, Alisa; Puig, Ana
Abstract : Limited research exists that examines the ethics of counselor educators' collaborative authorship practices. The study purpose was to explore the collaborative authorship decision‐making perceptions and practices of counselor educators ( N = 11). We identified six themes: (a) human process and communication, (b) context and nature of relationships, (c) learning experiences about authorship, (d) academic and career stage expectations, (e) collaborative authorship practices, and (f) philosophy of authorship. Implications and recommendations for research are discussed.